2022
DOI: 10.1002/marc.202200095
|View full text |Cite
|
Sign up to set email alerts
|

End Group Dye‐Labeled Polycarbonate Block Copolymers for Micellar (Immuno‐)Drug Delivery

Abstract: Defined conjugation of functional molecules to block copolymer end groups is a powerful strategy to enhance the scope of micellar carriers for drug delivery. In this study, an approach to access well-defined polycarbonate-based block copolymers by labeling their end groups with single fluorescent dye molecules is established. Following controlled polymerization conditions, the block copolymers' primary hydroxy end group can be converted into activated pentafluorophenyl ester carbonates and subsequently aminoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…For nanoparticle formation block copolymers of mPEG 44 - b -poly­(MTC-OBn) and mPEG 44 - b -poly­(MTC-NHBn) were, respectively, self-assembled to form polymeric micelles by the solvent evaporation method . Using this method, polymer chains are first dissolved in acetone and then added dropwise to water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For nanoparticle formation block copolymers of mPEG 44 - b -poly­(MTC-OBn) and mPEG 44 - b -poly­(MTC-NHBn) were, respectively, self-assembled to form polymeric micelles by the solvent evaporation method . Using this method, polymer chains are first dissolved in acetone and then added dropwise to water.…”
Section: Resultsmentioning
confidence: 99%
“…Especially for biological applications, functional polymers are needed to manufacture tailor-made materials. , Thus, tuning polymer functionalization provides the ability (a) to anchor or encapsulate therapeutic molecules, , (b) to enable a (triggered/stimuli-responsive) release, , and (c) to fine-tune polymer degradation. , Aliphatic polycarbonates are a promising material class in this regard due to their functionalizability by side chain introduction, biodegradability, and favorable toxicological profiles. ,,, Polycarbonate-based block copolymers were self-assembled into nanoparticular carriers and used for a variety of therapeutic applications. An important motif for functional polycarbonates are six-membered monomers derived from 2,2-bis­(hydroxymethyl)­propionic acid (bis-MPA) with a carboxy side chain substituent which, through esterification, can comprise a wide range of different functional groups. , An important monomer within this group is the hydrophobic 5-methyl-5-benzyloxycarbonyl-1,3-dioxan-2-one (MTC-OBn) that fosters block copolymer self-assembly into micellar nanoparticles and the encapsulation of hydrophobic (aromatic) compounds (supported by π–π stacking). , Alternatively, the development and polymerization of 5-methyl-5-pentafluorophenyloxycarbonyl-1,3-dioxane-2-one (MTC-PFP), a six-membered carbonate monomer with an active ester side chain motif, by Hedrick and co-workers enlarged the polycarbonate toolbox. , However, previously ROP of MTC-PFP was only achieved by using an acidic catalyst (e.g., trifluoromethanesulfonic acid) which, however, provided polymers of only moderate definition . Starting from poly­(MTC-PFP) postpolymerization, modification reactions access various materials by amine conjugation. , Polymeric materials accessed from both monomers were shown to be highly tolerable in vitro and even in vivo, and they can therefore be considered as biocompatible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They deliver immunomodulatory agents in the manner of physical encapsulation or chemical conjugation. [91][92][93] Agonists of STING and TLR, as well as inhibitors of indoleamine-2,3-dioxygenase (IDO), have been incorporated into the nanoscale delivery system, contributing to evading immune escape or potentiating ICI-based antitumor immune response for RT. 94,95 3.…”
Section: Basic Mechanismsmentioning
confidence: 99%
“…To broaden the scope of applications, a range of functional polycarbonates were designed and investigated as degradable materials for bioapplications and nanomedicine. [39,[49][50][51][52] Yet, for most of these structures, degradability was not investigated and just claimed by referring to the degradability of the archetypal, non-functionalized PTMC omitting further analysis to support the hypothesis. So far, it has been shown that polycarbonate degradability can be improved by increasing hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%